Do the right thing: Create event bubbles by requiring negative tests - Solaris, J. (2020)
As Covid-19 cases continue to rise worldwide, planning event bubbles may be the only chance to go back to in person events. Currently the biggest experiment in epidemiology is happening in Disney World with the NBA teams. This bubble includes locking down people in one controlled area for several weeks, testing continuously, and preventing contact with the outside world. In theory this sounds great, but when trying to recreate something similar for other events there are many important factors that need to be thought about.